Early Intervention Outcomes for Toddlers With Autism Spectrum Disorder and Their Families. Issue 3 (July 2018) - Noyes-Grosser, Donna M.; Elbaum, Batya; Wu, Yan; Siegenthaler, Kirsten M.; Cavalari, Rachel S.; Gillis, Jennifer M.; Romanczyk, Raymond G.
Abstract : Autism spectrum disorder (ASD) can be diagnosed as early as 18 months of age. State Early Intervention (EI) programs under Part C of the Individuals with Disabilities Education Act (IDEA) are serving increasing numbers of children with ASD; however, little is known about outcomes of these services. This study evaluated the impact of EI for toddlers with ASD ( n = 193) and other disabilities ( n = 129) and their families, using measures that included federal Part C outcome indicators. Children with ASD showed reduced maladaptive behaviors and improved social and communication skills on the PDD Behavior Inventory; some also made progress on the Part C child outcome indicators. Families of children with ASD reported that EI helped them achieve many outcomes identified as important to families participating in EI. Results provide a rich description of outcomes experienced by children with ASD and their families in one of the largest EI programs in the United States. Implications for results-driven accountability and future research are discussed. Abstract : Supplemental Digital Content is Available in the Text.